Hybrid nanocellulose-copper (ii) oxide as engine oil additives for tribological behavior improvement - Sakinah, Hisham; Kumaran, Kadirgama; Hussein, A. Mohammed; Kumar, Amit; Devarajan, Ramasamy; Mahendran, Samykano; Saidur, Rahman
Friction and wear are the main factors in the failure of the piston in automobile engines. The objective of this work was to improve the tribological behaviour and lubricant properties using hybrid Cellulose Nanocrystal (CNC) and Copper (II) oxide nanoparticles blended with SAE 40 as a base fluid. The two-step method was used in the hybrid nanofluid preparation. Three different concentrations were prepared in a range of 0.1% to 0.5%. Kinematic viscosity and viscosity index were also identified. The friction and wear behavior were evaluated using a tribometer based on ASTM G181. The CNC-CuO nano lubricant shows a significant improvement in term of viscosity index by 44.3–47.12% while for friction, the coefficient of friction (COF) decreases by 1.5%, respectively, during high and low-speed loads (boundary regime), and 30.95% during a high-speed, and low load (mixed regime). The wear morphologies results also show that a smoother surface was obtained after using CNC-CuO nano lubricant compared to SAE 40.